Cardiac Microvascular Dysfunction in Women Living With HIV Is Associated With Cytomegalovirus Immunoglobulin G. (11th September 2018) - Knudsen, Andreas; Thorsteinsson, Kristina; Christensen, Thomas E; Hasbak, Philip; Ripa, Rasmus Sejersten; Panum, Inge; Lebech, Anne-Mette; Kjaer, Andreas
Abstract: Background: People living with HIV (PLWH) appear to be at increased risk of cardiovascular disease (CVD), and this is possibly more pronounced in women living with HIV (WLWH). In the general population, men are more likely to develop obstructive coronary artery disease (CAD), and women often present with a nonobstructive pattern with cardiac microvascular dysfunction. We investigated cardiac microvascular function in men and women living with HIV and tested for association with cytomegalovirus (CMV) immunoglobulin G (IgG), as this has been associated with CVD in PLWH. Methods: In a cross-sectional study, 94 PLWH on antiretroviral therapy were scanned with 82 Rb positron emission tomography/computed tomography at rest and during adenosine-induced stress, which enables the quantification of the myocardial flow reserve (MFR). CMV IgG was measured in plasma. Results: WLWH had significantly lower MFR compared with men living with HIV (MLWH; P = .003), and >45% of the women had an MFR indicative of cardiac microvascular dysfunction, whereas this was only true for 24% of men ( P = .03). CMV IgG concentrations were inversely associated with MFR among WLWH but not MLWH ( P = .05 for interaction). Conclusions: In this first study comparing MFR in women and men living with HIV, we found that WLWH had significantly lower MFR than MLWH and 45% of the women had cardiac microvascular dysfunction despite younger age and lower cardiovascular risk. Furthermore, CMV IgG was inversely associated with MFR among women but not men. This calls for attention to CVD among young WLWH even with low cardiovascular risk.